HANDWASHING: AN OBSERVATION CONCERNING THE PRACTICE OF STANDARD PRECAUTIONS - Letícia Bertoldi; Daniele Laís Brandalize; Ana Paula de Oliveira Pacheco; Karin Rosa Persegona; Suzana Rodrigues do Nascimento (Universidade Federal do Paraná, 2000)
This work aims to verify if handwashing orientated by nursing professionals to the visitors before they have any contact with the patient. An Internation Unit of an University Hospital of Curitiba was randomly chosen. This is a describing study, a report of an experience that shows a non-participating investigation concerning handwashing practices, performed by its authors, in June of 2001, during visiting times. The study showed the absence of orientation for handwashing by the nursing team and also showed that is common the entrance of visitors straight to rooms and infirmaries, without previous orientation. It was also noticed the absence of orientation for the usage of glycerin alcohol 70%, although it was avaliable at the entry of each room, what may explain the non-usage of it by the visitors. It is clear that the role of nursing professionals concerning hospital infectation should be reconsidered. Health professionals should create conditions for allowing visiting without bringing any risk to patients nor to the visitors themselves, and for so, orientations must be used properly.